INVESTIGATING THE ROLE OF ACTIVE LEARNING IN ENHANCING WILLINGNESS TO COMMUNICATE AND SELFEFFICACY AMONG INDONESIAN SECONDARY-SCHOOL EFL LEARNERS - Lina Rachmawati; Slamet Asari; Nirwanto Maruf (University of Kuningan, 2025)
Active learning is increasingly recognized as a catalyst for improving both communicative behavior and psychological readiness in EFL classrooms. This study aimed to examine the effects of active learning on willingness to communicate (WTC) and self-efficacy among Indonesian eleventh-grade EFL students, and to explore the relationship between these constructs post-intervention. Employing a convergent parallel mixed-methods design, seventy students were assigned to experimental (active learning) and control (traditional instruction) groups for six weeks; data were collected via validated questionnaires, classroom observations, and interviews, and analyzed using t-tests, ANOVA, regression, and thematic analysis. Results showed that active learning produced large, significant gains in both WTC (Cohen’s d = 1.62) and self-efficacy (d = 1.79), with self-efficacy accounting for unique variance in post-intervention WTC (ΔR² = .18). Thematic analysis revealed that increased confidence and peer support were key mechanisms, as students described a shift from fear of mistakes to a focus on self-expression. Theoretically, the study extends Bandura’s self-efficacy theory into the L2 WTC domain and confirms the nested WTC model’s claim that instructional method can override dispositional barriers. Methodologically, this study offers a rigorous mixed-methods experiment in an Asian secondary-school EFL context, integrating fidelity checks, student voice, and robust effect-size estimation to strengthen validity and depth of interpretation. Practically, findings support integrating peer-teaching, scaffolding micro-presentations, and using selfefficacy pulse-checks. Results are generalizable to adolescent EFL learners in similar settings. Policy should promote active learning to foster communicative readiness. Future research should test the SE→WTC pathway in digital learning environments.